Independent and combined association of milk tea and takeaway food consumption on depression, anxiety, and comorbid symptoms among Chinese university students - Zhu, Juncheng; Lu, Jinkui; Tang, Lijun; Jin, Helin; Liu, Cong; Yuan, Xinping; Luo, Hao; He, Zhixiu; Song, Jiancai; Luo, Shuaicheng (Frontiers in Nutrition, 2026)
BackgroundMilk tea and takeaway food consumption are increasingly prevalent among Chinese university students and may contribute to adverse mental health outcomes. However, the combined association of these dietary behaviors on psychological symptoms remain unclear.MethodsA multicenter cross-sectional survey was conducted from September to November 2023 among 15,440 students from seven universities in four provinces of China. Single-factor associations between psychological symptom types and milk tea/takeaway food consumption were examined using the Chi-square test. Multivariate logistic regression was then employed to assess independent associations, adjusting for demographic and lifestyle confounders. Finally, interaction models were used to explore the combined association of milk tea and takeaway food consumption, as well as the impact of specific consumption combinations, on depression symptoms, anxiety symptoms, and their comorbidity. Odds ratios (OR) and 95% confidence intervals (CI) were calculated.ResultsMilk tea consumption was associated with an increased likelihood of only anxiety symptoms (OR = 1.33, 95% CI: 1.18–1.50) and comorbidity (OR = 1.16, 95% CI: 1.06–1.26). Takeaway food consumption was associated with only anxiety symptoms (OR = 1.23, 95% CI: 1.09–1.40). Students who consumed both milk tea and takeaway food had a higher risk of only anxiety symptoms (OR = 1.67, 95% CI: 1.43–1.95) and comorbidity (OR = 1.24, 95% CI: 1.11–1.38). Several specific consumption combinations—particularly cream cap milk tea with grilled/deep-fried skewers—were strongly linked to comorbidity (OR = 4.25, 95% CI: 3.61–5.02).ConclusionBoth milk tea and takeaway food consumption are independently associated with higher risks of anxiety symptoms and comorbid depression–anxiety among Chinese university students, with a significant combined association observed. High-fat, high-sugar milk tea combined with deep-fried or stir-fried takeaway food poses the greatest risk, highlighting the need for targeted dietary interventions to mitigate psychological symptom burden in this population.